A zinc-rich water-based paint and its preparation process
Through the two-component water-based coating formula, the use of modified asphalt and water-based epoxy resin emulsions has solved the environmental pollution and construction complexity of existing zinc-rich coatings, and improved the corrosion resistance, waterproof and mechanical properties of the coatings, which are suitable for corrosion protection and corrosion protection. Coating technology field.
Patent Information
- Application Number
- CN202411413518.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-10-11
AI Technical Summary
The existing zinc-rich coatings have high VOC content and environmental pollution problems, excellent solvent-based performance but insufficient weathering and heat resistance. The construction process of three-component water-based zinc-rich coatings is complex, which limits its use area.
Using two-component water-based coating formula, including components A and components B, component A contains modified bitumen and zinc powder, component B is an aqueous epoxy resin emulsion, which improves the coating by modifying lignin and modifiers. Anti-corrosion, waterproof and anti-aging properties, reduce the amount of zinc powder and improve mechanical properties.
It has achieved environmental friendliness, corrosion resistance, waterproofness and mechanical properties of epoxy zinc-rich paint, and the coating performance is long-term and stable, and is suitable for the technical field of anticorrosion coatings.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of anti-corrosion coatings, and in particular, relates to a zinc-rich water-based coating and a preparation process thereof. Background Art
[0002] With the large-scale application of steel, the problem of steel corrosion is also facing severe challenges. In order to reduce the damage caused by metal corrosion to steel, steel is sprayed with paint or coating after production to protect the steel and prevent it from corrosion.
[0003] Zinc-rich paint is a high-performance anti-corrosion paint that contains a large amount of zinc powder, usually more than 70% in the dry film. The anti-corrosion mechanism of zinc-rich paint mainly includes electrochemical protection, coating self-repair and passivation. Zinc powder acts as a sacrificial anode. When the zinc powder in the paint comes into contact with the steel surface, the zinc powder will be corroded first, thereby protecting the steel from corrosion. In addition, the corrosion products of zinc powder will form a dense protective film to further prevent the erosion of corrosive media. Due to its excellent performance, zinc-rich paints are widely used in the construction industry, machinery industry, power industry, as well as offshore platforms, ships, port facilities and other heavy corrosion protection fields. They can provide long-term anti-corrosion protection, especially in harsh marine environments.
[0004] Most of the common zinc-rich coatings on the market are solvent-based. Although they have excellent performance, they have high VOC content and cause great environmental pollution. In addition, zinc-rich coatings are exposed to the external environment for a long time and are constantly eroded by the sun and rain, which also puts great pressure on their weather resistance and heat resistance. Finally, because zinc is easy to react with water, water-based zinc-rich coatings are mostly multi-component coatings. The common water-based zinc-rich coatings on the market are mostly three-component systems, but the construction process of three-component water-based zinc-rich coatings is complicated, which causes great inconvenience to on-site construction spraying. It greatly limits its application field. Therefore, it is necessary to solve the above problems to meet higher demands in the field of anti-corrosion coating technology. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a zinc-rich water-based paint and a preparation process thereof.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A zinc-rich water-based paint, comprising a component A and a component B;
[0008] The component A comprises the following raw materials in parts by weight: 4-8 parts of curing agent, 0.2-1 parts of defoaming agent, 10-20 parts of modified asphalt, 60-80 parts of zinc powder, and 0.5-1 parts of dispersant;
[0009] The B component comprises the following raw materials in parts by weight: 20-30 parts of waterborne epoxy resin emulsion and 4-12 parts of water.
[0010] Furthermore, the curing agent is an amine curing agent.
[0011] Furthermore, the modified asphalt is prepared by the following steps:
[0012] A1. Add the dried and ground lignin into a flask, add pyridine and stir to fully dissolve it, then add acetic anhydride and seal the bottle mouth with a wooden stopper. Set the reaction temperature to 80°C and react for 12 hours. After the reaction is completed, filter, wash and dry to obtain acetylated lignin.
[0013] A2. Heat the asphalt to 200°C, set the shear rate to 1000r / min, slowly and uniformly add acetylated lignin under shear conditions, and set the shear time to 2h. After the shearing is completed, place the asphalt in a constant temperature oven at 180°C to allow the asphalt to swell and develop for 1h to obtain modified asphalt.
[0014] Furthermore, in step A1, the ratio of lignin, pyridine and acetic anhydride is 1 g: 20 mL: 5 mL.
[0015] Furthermore, in step A2, the ratio of asphalt to acetylated lignin is 3g:1g.
[0016] By modifying lignin, the hydroxyl groups in lignin are replaced by acetic acid groups in acetic anhydride, which improves the compatibility with asphalt and the thermal stability of lignin. In addition, the presence of a large number of aromatic ring structures, phenolic hydroxyl groups, carboxyl groups and other functional groups in lignin can enhance the anti-aging properties of asphalt to a certain extent. Moreover, asphalt is a complex black-brown mixture composed of hydrocarbons of different molecular weights and their non-metallic derivatives. It is an excellent waterproof, moisture-proof and anti-corrosion organic gelling material that can significantly enhance the anti-corrosion properties of zinc-rich coatings.
[0017] Furthermore, the waterborne epoxy resin emulsion is prepared by the following steps:
[0018] B1. In a three-necked flask equipped with a stirring reflux device, bisphenol epoxy resin, ethylene glycol diglycidyl ether and a modifier are mixed, and then 2-ethyl-4-methylimidazole (catalyst) is added. After stirring and mixing, nitrogen is introduced, and the reaction temperature is controlled to be 150° C., and reflux reaction is carried out for 6 hours to obtain a modified epoxy resin;
[0019] B2. Add the modified epoxy resin obtained in step B1, deionized water, and propylene glycol methyl ether into a flask and stir to reduce the viscosity of the epoxy resin. Then add polyethylene glycol monomethyl ether (emulsifier), heat the system to 65°C, and stir at high speed for 2 hours to obtain a water-based epoxy resin emulsion.
[0020] Furthermore, the raw materials are calculated in parts by weight as follows: 40-60 parts of bisphenol epoxy resin, 4-8 parts of ethylene glycol diglycidyl ether, 5-15 parts of modifier, 1-3 parts of 2-ethyl-4-methylimidazole, 60-80 parts of deionized water, 2-4 parts of propylene glycol methyl ether, and 6-12 parts of polyethylene glycol monomethyl ether.
[0021] Furthermore, the modifier is prepared by the following steps:
[0022] S1. In a three-necked flask equipped with a stirring reflux device, 2,2,6,6-tetramethylpiperidinol, n-octane and molybdenum trioxide were mixed and stirred uniformly, heated to 70°C, and then tert-butyl hydroperoxide aqueous solution was added dropwise. After the addition was completed, the reaction was refluxed for 5 hours, filtered, activated carbon was added to the filtrate, stirred for 1 hour, allowed to stand, filtered, the filtrate was taken, and n-octane was removed by vacuum distillation to obtain intermediate 1; the ratio of 2,2,6,6-tetramethylpiperidinol, n-octane, molybdenum trioxide and tert-butyl hydroperoxide aqueous solution was 15.6 g:51.4 g:0.2 g:25 mL;
[0023] Under the catalysis of molybdenum trioxide and the oxidation of tert-butyl hydroperoxide, 2,2,6,6-tetramethylpiperidinol and n-octane undergo a free radical coupling reaction; n-octane participates in the reaction process as a reactant and also acts as a reaction solvent, which can reduce the formation of by-products to obtain intermediate 1; the specific reaction process is as follows:
[0024]
[0025] S2. In a three-necked flask equipped with a stirring reflux device, the intermediate 1, glutaric acid and N,N-dimethylformamide (DMF) were mixed and stirred uniformly, and dicyclohexylcarbodiimide (DCC, dehydrating agent) and 4-dimethylaminopyridine (DMAP, catalyst) were added in sequence, and the reaction temperature was controlled to 75°C. The reaction was carried out for 6 hours. After the reaction was completed, the mixture was filtered, and part of the solvent was removed by rotary evaporation. The mixture was washed with anhydrous ethanol for 2-3 times, and vacuum dried to obtain the intermediate 2. The ratio of the amount of intermediate 1, glutaric acid, N,N-dimethylformamide, dicyclohexylcarbodiimide and 4-dimethylaminopyridine was 28.5g:15.4g:150mL:20.6g:0.3g.
[0026] Under the action of DCC and DMAP, intermediate 1 and glutaric acid undergo esterification reaction. By controlling the molar ratio of the two to be close to 1:1 and a slight excess of glutaric acid, only one carboxyl group on glutaric acid participates in the reaction to obtain intermediate 2. The specific reaction process is as follows:
[0027]
[0028] S3. In a three-necked flask equipped with a stirring device, the intermediate 2, 1,3-bis(aminopropyl)tetramethyldisiloxane and N,N-dimethylformamide were mixed and stirred evenly, dicyclohexylcarbodiimide was added, the device was placed in a water bath, and the reaction was kept at 55°C for 4 hours. After the reaction was completed, it was filtered, and part of the solvent was removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of ethyl acetate / petroleum ether, and the volume ratio of the two was 1:5), and the eluent was removed by rotary evaporation to obtain intermediate 3; the ratio of the amount of intermediate 2, 1,3-bis(aminopropyl)tetramethyldisiloxane, N,N-dimethylformamide, and dicyclohexylcarbodiimide was 39.9 g:25.1 g:150 mL:20.6 g;
[0029] The carboxyl group on intermediate 2 reacts with the amino group on 1,3-bis(aminopropyl)tetramethyldisiloxane to undergo an amidation reaction. Dicyclohexylcarbodiimide is used as a dehydrating agent to accelerate the reaction. By controlling the molar ratio of the two to be close to 1:1 and the 1,3-bis(aminopropyl)tetramethyldisiloxane to be slightly excessive, only one amino group on 1,3-bis(aminopropyl)tetramethyldisiloxane participates in the reaction to obtain intermediate 3. The specific reaction process is as follows:
[0030]
[0031] S4. In a three-necked flask equipped with a stirring device, p-phenylene diisocyanate, intermediate 3 and dimethyl sulfoxide (DMSO) were mixed, tributyltin (catalyst) was added and mixed and stirred evenly, the temperature was gradually increased to 65°C, and the mixture was kept warm for 8 hours. Stirring was continued during the reaction. After the reaction was completed, the solvent was removed by vacuum distillation, and the mixture was dried in vacuo to obtain a modifier; the ratio of p-phenylene diisocyanate, intermediate 3, dimethyl sulfoxide and tributyltin was 17.4 g:62.9 g:150 mL:3 g;
[0032] The isocyanate group in p-phenylene diisocyanate reacts with the amino group on the intermediate 3 to generate a urea group. By controlling the molar ratio of the two to be close to 1:1 and a slight excess of p-phenylene diisocyanate, only one isocyanate group on p-phenylene diisocyanate participates in the reaction to obtain a modifier. The specific reaction process is as follows:
[0033]
[0034] The modifier molecule prepared by the present invention contains -Si-O-Si-chain segments, hindered amines, long carbon chains and isocyanate structures, wherein the Si-O bonds of the -Si-O-Si-chain segments have high bond energy and good stability, and can improve the heat resistance, water resistance and corrosion resistance of the matrix; the introduction of hindered amine groups can effectively capture free radicals generated in photo-oxidative degradation, inhibit the photo-oxidative degradation of the matrix, and can be regenerated under stable conditions, thereby improving the anti-light aging performance of the matrix; the long carbon chain is a methylene chain segment, which belongs to a flexible chain segment, and can not only improve the mechanical properties of the matrix, but also further enhance the water resistance of the matrix; finally, the isocyanate groups in the modifier molecules react with the epoxy groups in the epoxy resin matrix under the action of a catalyst to generate a five-membered ring oxazolidinone structure, and the structure can further improve the mechanical properties and heat resistance of the epoxy resin matrix; in addition, the modifier is connected to the epoxy resin matrix through chemical bonds, thereby improving the migration resistance and exudation resistance of the small molecules of the modifier, and improving the stability of the modifier.
[0035] Beneficial effects of the present invention:
[0036] 1. The epoxy zinc-rich paint prepared by the present invention is a two-component water-based paint. Compared with ordinary epoxy zinc-rich paint, it reduces the amount of zinc powder, improves the mechanical properties of the paint, and is environmentally friendly;
[0037] 2. With epoxy resin as the matrix, the coating has excellent corrosion resistance and waterproof properties;
[0038] 3. Adding modified lignin to asphalt not only improves the compatibility of the two, but also improves the corrosion resistance, waterproofness and anti-aging properties of the coating;
[0039] 4. The various groups in the prepared modifier molecules work synergistically, which can greatly enhance the heat resistance, water resistance, corrosion resistance and mechanical properties of epoxy resin, thereby improving the various properties of the coating, and the performance is long-term and stable;
[0040] Therefore, the water-based zinc-rich coating prepared by the present invention has stable and efficient heat resistance, water resistance, corrosion resistance and mechanical properties, good aging resistance, is environmentally friendly, and has important application value in the field of anti-corrosion coating technology. DETAILED DESCRIPTION
[0041] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] Example 1, preparation of modifier:
[0043] S1. In a three-necked flask equipped with a stirring reflux device, 15.6 g of 2,2,6,6-tetramethylpiperidinol, 51.4 g of n-octane, and 0.2 g of molybdenum trioxide were mixed and stirred evenly, heated to 70°C, and 25 mL of tert-butyl hydroperoxide aqueous solution was added dropwise. After the addition was completed, the reaction was refluxed for 5 h, filtered, activated carbon was added to the filtrate, stirred for 1 h, allowed to stand, filtered, the filtrate was taken, and n-octane was removed by vacuum distillation to obtain intermediate 1;
[0044] S2. In a three-necked flask equipped with a stirring reflux device, 28.5 g of intermediate 1, 15.4 g of glutaric acid and 150 mL of N,N-dimethylformamide were mixed and stirred evenly, and 20.6 g of dicyclohexylcarbodiimide and 0.3 g of 4-dimethylaminopyridine were added in sequence. The reaction temperature was controlled to 75 ° C. The reaction was carried out for 6 hours. After the reaction was completed, it was filtered, and part of the solvent was removed by rotary evaporation. The product was washed with anhydrous ethanol twice and dried in vacuo to obtain intermediate 2;
[0045] S3, in a three-necked flask equipped with a stirring device, 39.9 g of intermediate 2, 25.1 g of 1,3-bis(aminopropyl)tetramethyldisiloxane and 150 mL of N,N-dimethylformamide were mixed and stirred evenly, 20.6 g of dicyclohexylcarbodiimide was added, the device was placed in a water bath, and the reaction was kept at 55° C. for 4 h. After the reaction was completed, it was filtered, and part of the solvent was removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of ethyl acetate / petroleum ether, and the volume ratio of the two was 1:5), and the eluent was removed by rotary evaporation to obtain intermediate 3;
[0046] S4. In a three-necked flask equipped with a stirring device, 17.4 g of p-phenylene diisocyanate, 62.9 g of intermediate 3 and 150 mL of dimethyl sulfoxide were mixed, 3 g of tributyltin was added and the mixture was stirred evenly, the temperature was gradually increased to 65°C, and the mixture was kept warm for 8 h. Stirring was continued during the reaction. After the reaction was completed, the solvent was removed by distillation under reduced pressure, and the mixture was dried in vacuo to obtain a modifier.
[0047] Example 2, preparation of modifier:
[0048] S1. In a three-necked flask equipped with a stirring reflux device, 31.2 g of 2,2,6,6-tetramethylpiperidinol, 102.8 g of n-octane, and 0.4 g of molybdenum trioxide were mixed and stirred evenly, heated to 70°C, and 50 mL of tert-butyl hydroperoxide aqueous solution was added dropwise. After the addition was completed, the reaction was refluxed for 5 h, filtered, activated carbon was added to the filtrate, stirred for 1 h, allowed to stand, filtered, the filtrate was taken, and n-octane was removed by vacuum distillation to obtain intermediate 1;
[0049] S2. In a three-necked flask equipped with a stirring reflux device, 57.0 g of intermediate 1, 30.8 g of glutaric acid and 300 mL of N,N-dimethylformamide were mixed and stirred evenly, and 41.2 g of dicyclohexylcarbodiimide and 0.6 g of 4-dimethylaminopyridine were added in sequence. The reaction temperature was controlled to 75 ° C. The reaction was carried out for 6 hours. After the reaction was completed, it was filtered, and part of the solvent was removed by rotary evaporation. The product was washed with anhydrous ethanol twice and dried in vacuo to obtain intermediate 2;
[0050] S3, in a three-necked flask equipped with a stirring device, 79.8g of intermediate 2, 50.2g of 1,3-bis(aminopropyl)tetramethyldisiloxane and 300mL of N,N-dimethylformamide were mixed and stirred evenly, 41.2g of dicyclohexylcarbodiimide was added, the device was placed in a water bath, and the reaction was kept at 55°C for 4h. After the reaction was completed, the reaction was filtered, and part of the solvent was removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of ethyl acetate / petroleum ether, and the volume ratio of the two was 1:5), and the eluent was removed by rotary evaporation to obtain intermediate 3;
[0051] S4. In a three-necked flask equipped with a stirring device, 34.8 g of p-phenylene diisocyanate, 125.8 g of intermediate 3 and 300 mL of dimethyl sulfoxide were mixed, 6 g of tributyltin was added and the mixture was stirred evenly, the temperature was gradually increased to 65°C, and the mixture was kept warm for 8 hours with continuous stirring during the reaction. After the reaction was completed, the solvent was removed by distillation under reduced pressure, and the mixture was dried in vacuo to obtain a modifier.
[0052] Example 3: Preparation of water-based epoxy resin emulsion:
[0053] B1. In a three-necked flask equipped with a stirring reflux device, 40 g of bisphenol epoxy resin (epoxy value 0.54), 4 g of ethylene glycol diglycidyl ether and 5 g of the modifier prepared in Example 1 were mixed, and then 1 g of 2-ethyl-4-methylimidazole was added. After stirring and mixing, nitrogen was introduced, the reaction temperature was controlled to 150° C., and refluxed for 6 h to obtain a modified epoxy resin;
[0054] B2. Add the modified epoxy resin obtained in step B1, 60 g of deionized water, and 2 g of propylene glycol methyl ether into a flask and stir to reduce the viscosity of the epoxy resin. Then add 6 g of polyethylene glycol monomethyl ether, heat the system to 65°C, and stir at high speed for 2 hours to obtain a water-based epoxy resin emulsion.
[0055] Example 4: Preparation of water-based epoxy resin emulsion:
[0056] B1. In a three-necked flask equipped with a stirring reflux device, 50 g of bisphenol epoxy resin (epoxy value 0.54), 6 g of ethylene glycol diglycidyl ether and 10 g of the modifier prepared in Example 2 were mixed, and then 2 g of 2-ethyl-4-methylimidazole was added. After stirring and mixing, nitrogen was introduced, the reaction temperature was controlled to 150° C., and refluxed for 6 h to obtain a modified epoxy resin;
[0057] B2. Add the modified epoxy resin obtained in step B1, 70 g of deionized water, and 3 g of propylene glycol methyl ether into a flask and stir to reduce the viscosity of the epoxy resin. Then add 8 g of polyethylene glycol monomethyl ether, heat the system to 65°C, and stir at high speed for 2 hours to obtain a water-based epoxy resin emulsion.
[0058] Example 5: Preparation of water-based epoxy resin emulsion:
[0059] B1. In a three-necked flask equipped with a stirring reflux device, 60 g of bisphenol epoxy resin (epoxy value 0.54), 8 g of ethylene glycol diglycidyl ether and 15 g of the modifier prepared in Example 2 were mixed, and 3 g of 2-ethyl-4-methylimidazole was added. After stirring and mixing, nitrogen was introduced, the reaction temperature was controlled to 150° C., and refluxed for 6 h to obtain a modified epoxy resin;
[0060] B2. Add the modified epoxy resin obtained in step B1, 80 g of deionized water, and 4 g of propylene glycol methyl ether into a flask and stir to reduce the viscosity of the epoxy resin. Then add 12 g of polyethylene glycol monomethyl ether, heat the system to 65°C, and stir at high speed for 2 hours to obtain a water-based epoxy resin emulsion.
[0061] Example 6: Preparation of modified asphalt:
[0062] A1. Add 1 g of dried and ground lignin into a flask, add 20 mL of pyridine and stir to fully dissolve it, then add 5 mL of acetic anhydride and seal the bottle mouth with a wooden stopper. Set the reaction temperature to 80 ° C and react for 12 hours. After the reaction is completed, filter, wash and dry to obtain acetylated lignin;
[0063] A2. Heat 3g of asphalt to 200℃, set the shear rate to 1000r / min, slowly and uniformly add 1g of acetylated lignin under shear conditions, and set the shear time to 2h. After the shearing is completed, place it in a constant temperature oven at 180℃ to allow the asphalt to swell and develop for 1h to obtain modified asphalt.
[0064] Example 7: Preparation of zinc-rich water-based coating:
[0065] Component A:
[0066] 4 g of ethylenediamine (curing agent), 10-20 g of the modified asphalt prepared in Example 6, 0.2 g of an organosilicon defoamer and 0.5 g of a polyacrylate (dispersant) were mixed and stirred at 1000 r / min for 15 min, and 60 g of zinc powder was added and ground to 60 μm using a sand mill to obtain component A.
[0067] Component B:
[0068] 20 g of the aqueous epoxy resin emulsion prepared in Example 3 was mixed with 4 g of water, and stirred at 800 r / min for 20 min to obtain component B;
[0069] Component A and component B are stirred and mixed evenly in a mass ratio of 1:2 to obtain a zinc-rich water-based paint.
[0070] Example 8: Preparation of zinc-rich water-based coating:
[0071] Component A:
[0072] 6 g of triethylamine, 15 g of the modified asphalt prepared in Example 6, 0.6 g of an organosilicon defoamer and 0.7 g of a polyacrylate were mixed and stirred at 1000 r / min for 15 min, and 70 g of zinc powder was added and ground to a fineness of 60 μm using a sand mill to obtain component A;
[0073] Component B:
[0074] 25 g of the aqueous epoxy resin emulsion prepared in Example 4 was mixed with 8 g of water, and stirred at 800 r / min for 20 min to obtain component B;
[0075] Component A and component B are stirred and mixed evenly in a mass ratio of 1:2 to obtain a zinc-rich water-based paint.
[0076] Example 9: Preparation of zinc-rich water-based coating:
[0077] Component A:
[0078] 8 g of triethylamine, 20 g of the modified asphalt prepared in Example 6, 1 g of an organosilicon defoamer and 1 g of a polyacrylate were mixed and stirred at 1000 r / min for 15 min, and 80 g of zinc powder was added and ground to a fineness of 60 μm using a sand mill to obtain component A;
[0079] Component B:
[0080] 30 g of the aqueous epoxy resin emulsion prepared in Example 5 was mixed with 12 g of water, and stirred at 800 r / min for 20 min to obtain component B;
[0081] Component A and component B are stirred and mixed evenly in a mass ratio of 1:2 to obtain a zinc-rich water-based paint.
[0082] In comparative example 1, a commercially available water-based epoxy resin emulsion was used to replace the water-based epoxy resin emulsion in Example 9, and the remaining steps were the same as those in Example 9 to prepare a coating.
[0083] In comparative example 2, a commercially available hot water resistant zinc-rich paint was used.
[0084] The following performance tests were performed on Examples 7, 8 and 9 and Comparative Examples 1 and 2 according to different test standards:
[0085] Adopt the national standard GB / T 9286-2021 "Scratch test method for paints and varnishes" to measure adhesion;
[0086] The non-volatile matter content was measured using the national standard GBT 1725-2007 "Determination of non-volatile matter content of paints, varnishes and plastics";
[0087] The national standard GB / T 1732-2020 "Determination of impact resistance of paint film" is used to measure the impact resistance of the sample before and after standing at 180°C for 12 hours;
[0088] The water resistance is measured using the national standard GB / T 1733-1993 "Determination of water resistance of paint films";
[0089] The national standard GB / T 1865-2009 is used to measure the aging resistance and the GB / T 1766 standard is used for rating;
[0090] The national standard GB / T 1763 "Determination of chemical resistance of paint film" is used to determine the acid and alkali resistance;
[0091] The measured results are shown in the following table:
[0092]
[0093] It can be seen from the above table that the water-based zinc-rich coating prepared in the embodiment of the present invention has higher aging resistance, heat resistance, water resistance, corrosion resistance and mechanical properties than the control example, and has a high non-volatile matter content and less environmental pollution, and has important application value in the field of anti-corrosion coating technology.
[0094] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0095] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A zinc-rich water-based paint, characterized in that: It comprises component A and component B, wherein component A comprises 4-8 parts of curing agent, 0.2-1 parts of defoaming agent, 10-20 parts of modified asphalt, 60-80 parts of zinc powder, and 0.5-1 parts of dispersant, and component B comprises 20-30 parts of waterborne epoxy resin emulsion and 4-12 parts of water, according to weight parts; Wherein, the water-based epoxy resin emulsion is prepared by the following steps: B1, bisphenol epoxy resin, ethylene glycol diglycidyl ether and a modifier are mixed, and 2-ethyl-4-methylimidazole is added, and after stirring and mixing, nitrogen is introduced, and reflux reaction is carried out at 150° C. for 6 hours to obtain a modified epoxy resin; B2, add the modified epoxy resin prepared in step B1, deionized water, and propylene glycol methyl ether into a flask, stir, add polyethylene glycol monomethyl ether, and stir at high speed at 65° C. for 2 h to obtain a water-based epoxy resin emulsion; Wherein, the modifier is prepared by the following steps: S1. Mix 2,2,6,6-tetramethylpiperidinol, n-octane and molybdenum trioxide and stir evenly. Heat to 70°C, then drop tert-butyl hydroperoxide solution. After the addition is complete, reflux for 5 hours, filter, add activated carbon to the filtrate, stir for 1 hour, let stand, filter, take the filtrate, and distill under reduced pressure to obtain intermediate 1. S2, mixing intermediate 1, glutaric acid and N,N-dimethylformamide and stirring evenly, adding dicyclohexylcarbodiimide and 4-dimethylaminopyridine in sequence, reacting at 75°C for 6 hours, filtering, rotary evaporating, washing and drying to obtain intermediate 2; S3, mixing intermediate 2, 1,3-bis(aminopropyl)tetramethyldisiloxane and N,N-dimethylformamide, adding dicyclohexylcarbodiimide, reacting at 55° C. for 4 h, filtering, rotary evaporating, column chromatography purification, and rotary evaporating to obtain intermediate 3; S4. Mix p-phenylene diisocyanate, intermediate 3 and dimethyl sulfoxide, add tributyltin and stir evenly, gradually increase the temperature to 65°C, and keep the reaction for 8 hours. Stir continuously during the reaction. After the reaction is completed, distill under reduced pressure and dry in vacuum to obtain a modifier.
2. A zinc-rich water-based paint according to claim 1, characterized in that: In step S1, the ratio of the amount of 2,2,6,6-tetramethylpiperidinol, n-octane, molybdenum trioxide, and tert-butyl hydroperoxide aqueous solution is 15.6 g:51.4 g:0.2 g:25 mL.
3. A zinc-rich water-based paint according to claim 1, characterized in that: In step S2, the ratio of the amount of intermediate 1, glutaric acid, N,N-dimethylformamide, dicyclohexylcarbodiimide, and 4-dimethylaminopyridine is 28.5 g: 15.4 g: 150 mL: 20.6 g: 0.3 g.
4. A zinc-rich water-based paint according to claim 1, characterized in that: In step S3, the ratio of the amount of intermediate 2, 1,3-bis(aminopropyl)tetramethyldisiloxane, N,N-dimethylformamide, and dicyclohexylcarbodiimide is 39.9 g:25.1 g:150 mL:20.6 g.
5. A zinc-rich water-based paint according to claim 1, characterized in that: In step S4, the ratio of the amount of p-phenylene diisocyanate, intermediate 3, dimethyl sulfoxide and tributyltin is 17.4 g:62.9 g:150 mL:3 g.
6. A zinc-rich water-based paint according to claim 1, characterized in that: The raw materials are calculated in parts by weight as follows: 40-60 parts of bisphenol epoxy resin, 4-8 parts of ethylene glycol diglycidyl ether, 5-15 parts of modifier, 1-3 parts of 2-ethyl-4-methylimidazole, 60-80 parts of deionized water, 2-4 parts of propylene glycol methyl ether, and 6-12 parts of polyethylene glycol monomethyl ether.
7. A zinc-rich water-based paint according to claim 1, characterized in that: The modified asphalt is prepared by the following steps: A1. Add lignin into a flask, add pyridine and stir, then add acetic anhydride, react at 80°C for 12h, and filter, wash and dry to obtain acetylated lignin; A2. Heat the asphalt to 200°C, set the shear rate to 1000r / min, slowly and uniformly add acetylated lignin under shear conditions, and set the shear time to 2h. After the shearing is completed, place the asphalt in an oven to allow it to swell and develop for 1h to obtain modified asphalt.
8. A process for preparing a zinc-rich water-based paint according to claim 1, characterized in that: The following steps are involved: After mixing the curing agent, modified asphalt, defoaming agent and dispersant, zinc powder is added to obtain component A; then the water-based epoxy resin emulsion is stirred and mixed with water to obtain component B; component A and component B are stirred and mixed evenly at a mass ratio of 1:2 to obtain a zinc-rich water-based coating.
Citation Information
Patent Citations
Self-emulsifying aqueous epoxide resin paint and method for producing the same
CN101220237A
Epoxy resin adhesive and preparation method thereof
CN111548760A
Electric-penetration-resistant coating and production process thereof
CN117025033A
Low-voltage fireproof cable and preparation method thereof
CN117423494A
Weather-resistant waterborne epoxy resin coating and preparation method thereof
CN117701101A
